Acute Occlusions of Dual-Layer Carotid Stents After Endovascular Emergency Treatment of Tandem Lesions. Issue 8 (August 2017) - Yilmaz, Umut; Körner, Heiko; Mühl-Benninghaus, Ruben; Simgen, Andreas; Kraus, Catherine; Walter, Silke; Behnke, Stefanie; Faßbender, Klaus; Reith, Wolfgang; Unger, Marcus M.
Abstract : Background and Purpose—: A new generation of carotid artery stents that uses a second micromesh layer to reduce embolic events during carotid artery stenting has recently been introduced. The purpose of this study was to compare acute occlusion rates of these new dual-layer stents with those of single-layer stents in the setting of emergency carotid artery stenting with intracranial mechanical thrombectomy in acute ischemic stroke. Methods—: Consecutive patients with acute tandem (intra- and extracranial) lesions of the anterior circulation who were endovascularly treated at our institution were identified from our registry of neuroendovascular interventions. Clinical, angiographic, and neuroimaging data were analyzed. End points included acute occlusions of the carotid stents (within 72 hours after stenting) and symptomatic intracerebral hemorrhage. Results—: Forty-seven patients were included. Dual-layer stents (n=20) had a significantly higher rate of acute occlusions than single-layer stents (n=27; 45% versus 3.7%; P =0.001; odds ratio, 21.3; 95% confidence interval, 2.4–188.4). There were no significant differences in the rates of patients who had any antiplatelet or dual antiplatelet medication before admission, in the rates of postinterventional symptomatic intracerebral hemorrhage, the mean National Institutes of Health Stroke Scale scores at admission, or the modified Rankin Scale scores at discharge. Conclusions—: The recently introduced dual-layer stents have a higher risk of acute occlusion compared with single-layer stents in the treatment of acute stroke.